Technology Adoption, Turbulence and the Dynamics of Unemployment - Georg Dürnecker (University of Mannheim, Department of Economics, 2011)
The divergence of unemployment rates between the United States and Europe coincided with a substantial acceleration in capital-embodied technical change in the late 1970s. Evidence suggests that European economies have lagged behind the United States in the adoption and usage of new technologies. This paper argues that the obsolescence of an economy's technological capital is a key determinant for the way the economy's labor market reacts to an acceleration in capital-embodied technical change. The proposed framework offers a novel explanation for the observed divergence of unemployment rates across economies that are hit by the very same shock (i.e. the acceleration in embodied technical change) but differ in their technology adoption. The results of the paper challenge the popular, but controversial, view that blames generous unemployment insurance for high unemployment in Europe. The analysis shows that the observed institutional heterogeneity is insufficient to explain the diverse evolution of unemployment rates.
urn:nbn:de:bsz:180-madoc-296405
Keywords: J24; J64; O33; 330; unemployment; matching; turbulence; technology choice; capital-embodied technical change; skill loss